From N-vinylpyrrolidone anions to modified paraffin-like oligomers via double alkylation with 1,8-dibromooctane: access to covalent networks and oligomeric amines for dye attachment - Obels, Daniela; Lievenbrück, Melanie; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2016)
The double alkylation of N-vinylpyrrolidone (N-VP) with 1,8-dibromooctane yields paraffin-like oligomeric chains bearing polymerizable vinyl moieties. These oligomers were radically crosslinked in bulk with N-VP as co-monomer yielding swellable polymer disks. The vinylic side groups of the N-VP oligomers allow thiol–ene click reactions with 2-aminoethanethiol hydrochloride to obtain reactive amino-functionalized oligomers. Further modification of the free amino groups with 1,4-difluoro-9,10-anthraquinone (DFA) yields red-colored oligomeric anthraquinone dyes. The final reaction of DFA-substituted N-VP oligomers with Jeffamine® M 600 leads to blue-colored and branched oligomers with poly(ethylene glycol) side chains.
Keywords: double alkylation; modified N-vinylpyrrolidone; oligomeric anthraquinone dye; paraffin-like oligomer; radical thiol-ene click reaction

(untitled) - Hecht, G.; Scholtan, W. (Z. Gesamte Exp. Med., 1959)

(untitled) - Scholtan, W. (Makromol. Chem., 1953)

(untitled) - Schmidt, K. (Klin. Wochenschr., 1979)

(untitled) - Patat, F.; Estupinan, L. (Makromol. Chem., 1961)

(untitled) - Vijayasekaran, S.; Chirila, T. V.; Hong, Y.; Tahija, S. G.; Dalton, P. D.; Constable, I. J.; McAllister, I. L. (J. Biomater. Sci., Polym. Ed., 1996)

(untitled) - Göthlich, A.; Koltzenburg, S.; Schornick, G. (Chem. Unserer Zeit, 2005)

(untitled) - Fischer, F.; Bauer, S. (Chem. Unserer Zeit, 2009)

(untitled) - Haaf, F.; Sanner, A.; Straub, F. (Polym. J., 1985)

(untitled) - Franzmann, G.; Ringsdorf, H. (Makromol. Chem., 1976)

(untitled) - Kaneda, Y.; Tsutsumi, Y.; Yoshioka, Y.; Kamada, H.; Yamamoto, Y.; Kodaira, H.; Tsunoda, S.-i.; Okamoto, T.; Mukai, Y.; Shibata, H.; Nagakawa, S.; Mayumi, T. (Biomaterials, 2004)

(untitled) - Gómez-Tardajos, M.; Pino-Pinto, J. P.; Díaz-Soto, C.; Flores, M. E.; Gallardo, A.; Elvira, C.; Reinecke, H.; Nishide, H.; Moreno-Villoslada, I. (Dyes Pigm., 2013)

(untitled) - Widanapathirana, L.; Tale, S.; Reineke, T. M. (Mol. Pharmaceutics, 2015)

(untitled) - Bencini, M.; Ranucci, E.; Ferruti, P.; Oldani, C.; Licandro, E.; Maiorana, S. (Macromolecules, 2005)

(untitled) - He, W.; Gonsalves, K. E.; Pickett, J. H.; Halberstadt, C. (Biomacromolecules, 2003)

(untitled) - del Prado, A.; Navarro, R.; Gallardo, A.; Elvira, C.; Reinecke, H. (RSC Adv., 2014)

(untitled) - Trellenkamp, T.; Ritter, H. (Macromolecules, 2010)

(untitled) - Trellenkamp, T.; Ritter, H. (Macromol. Rapid Commun., 2009)

(untitled) - del Prado, A.; Navarro, R.; Levkin, P.; Gallardo, A.; Elvira, C.; Reinecke, H. (J. Polym. Sci., Part A: Polym. Chem., 2016)

(untitled) - Pérez Perrino, M.; Navarro, R.; Gómez Tardajos, M.; Gallardo, A.; Reinecke, H. (Eur. Polym. J., 2010)

(untitled) - Pérez Perrino, M.; Navarro, R.; Gómez Tardajos, M.; Gallardo, A.; Reinecke, H. (Macromol. Chem. Phys., 2009)

(untitled) - Tardajos, M. G.; Nash, M.; Rochev, Y.; Reinecke, H.; Elvira, C.; Gallardo, A. (Macromol. Chem. Phys., 2012)

(untitled) - Tardajos, M. G.; Aranaz, I.; Pérez, M.; López, D.; Reinecke, H.; Elvira, C.; Gallardo, A. (Macromolecules, 2013)

(untitled) - Schönenberg, L.; Ritter, H. (Macromol. Chem. Phys., 2015)

(untitled) - Obels, D.; Siegfeld, P.; Ritter, H. (Polym. Int., 2016)

(untitled) - White, L. A.; Jönson, S.; Hoyle, C. E.; Mathias, L. J. (Polymer, 1999)

(untitled) - Engström, J. U. A.; Helgee, B. (J. Comb. Chem., 2006)

(untitled) - Eldridge, R. B. (Ind. Eng. Chem. Res., 1993)

(untitled) - Elder, R. (J. Am. Coll. Toxicol., 1984)

(untitled) - Bayen, S.; Obbard, J. P.; Thomas, G. O. (Environ. Int., 2006)

Chlorinated paraffins - de Boer, J.; Hutzinger, O.; T. E.-S., Ali (Springer, 2010)

(untitled) - Panzel, H.; Ballschmiter, K. (Fresenius' Z. Anal. Chem., 1974)

(untitled) - Alkan, C. (Thermochim. Acta, 2006)

e-EROS Encyclopedia of Reagents for Organic Synthesis - Iwema Bakker, W. I.; Lee Wong, P.; Snieckus, V.; Warrington, J. M.; Barriault, L. (Wiley, 2001)

(untitled) - Reetz, M. T.; Maier, W. F. (Liebigs Ann. Chem., 1980)

(untitled) - Sánchez-Chaves, M.; Martínez, G.; López Madruga, E.; Fernández-Monreal, C. (J. Polym. Sci., Part A: Polym. Chem., 2002)

(untitled) - Ganji, F.; Vasheghani-Farahani, S.; Vasheghani-Farahani, E. (Iran. Polym. J., 2010)

(untitled) - Colombo, P. (Adv. Drug Delivery Rev., 1993)

(untitled) - Mathur, A. M.; Moorjani, S. K.; Scranton, A. B. (J. Macromol. Sci., Rev. Macromol. Chem. Phys., 1996)

(untitled) - Hoyle, C. E.; Bowman, C. N. (Angew. Chem., Int. Ed., 2010)

(untitled) - Dondoni, A. (Angew. Chem., 2008)

U. S. Patent - Parakka, J.; McCrea, K. R.; Ward, R. S. (PDMS-PVP block copolymers, 2012)

(untitled) - Krapcho, A. P.; Getahun, Z. (Synth. Commun., 1985)

(untitled) - Jacquemin, D.; Preat, J.; Charlot, M.; Wathelet, V.; André, J.-M.; Perpète, E. A. (J. Chem. Phys., 2004)

(untitled) - Diaz, A. N. (J. Photochem. Photobiol., A: Chem., 1990)